Placebo-Controlled Efficacy of Percutaneous Coronary Intervention for Focal and Diffuse Patterns of Stable Coronary Artery Disease. (3rd August 2021) - Rajkumar, Christopher A.; Shun-Shin, Matthew; Seligman, Henry; Ahmad, Yousif; Warisawa, Takayuki; Cook, Christopher M.; Howard, James P.; Ganesananthan, Sashiananthan; Amarin, Laura; Khan, Caitlin; Ahmed, Ayesha; Nowbar, Alexandra; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Physiological assessment with pressure wire pullback can characterize coronary artery disease (CAD) with a focal or diffuse pattern. However, the clinical relevance of this distinction is unknown. We use data from the ORBITA trial (Objective Randomised Blinded Investigation With Optimal Medical Therapy of Angioplasty in Stable Angina) to test if the pattern of CAD predicts the placebo-controlled efficacy of percutaneous coronary intervention (PCI) on stress echocardiography ischemia and symptom end points. Methods: One hundred sixty-four patients in ORBITA underwent blinded instantaneous wave-free ratio (iFR) pullback assessment before randomization. Focal disease was defined as a ≥0.03 iFR unit drop within 15 mm, rather than over a longer distance. Analyses were performed using regression modeling. Results: In the PCI arm (n=85), 48 were focal and 37 were diffuse. In the placebo arm (n=79), 35 were focal and 44 were diffuse. Focal stenoses were associated with significantly lower fractional flow reserve (FFR) and iFR values than diffusely diseased vessels (mean FFR and iFR, focal 0.60±0.15 and 0.65±0.24, diffuse 0.78±0.10 and 0.88±0.08, respectively, P <0.0001). With adjustment for this difference, PCI for focal stenoses resulted in significantly greater reduction in stress echo ischemia than PCI for diffuse disease ( P <0.05). The effect of PCI on between-arm pre-randomization adjusted exercise time was 9.32 seconds (95% CI, −17.1 to 35.7 seconds; P =0.487). When stratified for pattern of disease, there was no detectable difference between focal and diffuse CAD ( P interaction=0.700). PCI improved Seattle Angina Questionnaire angina frequency score and freedom from angina more than placebo ( P =0.034; P =0.0035). However, there was no evidence of interaction between the physiological pattern of CAD and these effects ( P interaction=0.436; P interaction=0.908). Conclusions: PCI achieved significantly greater reduction of stress echocardiography ischemia in focal compared with diffuse CAD. However, for symptom end points, no such difference was observed. Registration: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT02062593.